Another South : experimental writing in the South - Lavender, Bill, 1951- (Modern and contemporary poetics., 2003)
Another South is an anthology of poetry from contemporary southern writers who are working in forms that are radical, innovative, and visionary. Highly experimental and challenging in nature, the poetry in this volume, with its syntactical disjunctions, formal revolutions, and typographic playfulness, represents the direction of a new breed of southern writing that is at once universal in its appeal and regional in its flavor. Focusing on poets currently residing in the South, the anthology includes both emerging and established voices in the national and internati.